PENGEMBANGAN MODEL PEMBELAJARAN IPS BERBASIS INKUIRI SOSIAL (SOCIAL INQUIRY) DALAM MEMBENTUK KARAKTER PEDULI SOSIAL DI SD - Suminah Suminah (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: the current study was intended to develop social inquiry based social science teaching and learning to build the social awareness in elementary schools. The development processes were preliminary study, model development, model tryout. The results of the development included (1) lesson plans of social science for elementary schools, and (2) the social inquiry based social science teaching and learning model which was appropriate, valid, and effective to achieve the goals of the teaching and learning. The result of this study which was the social inquiry based social science teaching and learning model should be implemented by elementary school teachers in building the social awareness.Keywords: social science teaching and learning, social inquiry, character building, elementary schools.Abstrak: Penelitian ini bertujuan untuk mengembangkan model pembelajaran IPS berbasis inkuiri sosial dalam membentuk karakter peduli sosial. Langkah pengembangan meliputi studi pendahuluan, pengembangan model, dan uji model. Hasil pengembangan meliputi (1) Rencana Pelaksanaan Pembelajaran (RPP) IPS SD, dan (2) model pembelajaran IPS berbasis inkuiri sosial yang layak, valid, dan efektif untuk mencapai tujuan pembelajaran. Model pembelajaran IPS berbasis inkuiri sosial hasil penelitian ini disarankan untuk diimplementasikan oleh para guru di SD dalam membentuk karakter peduli sosial.Kata kunci: pembelajaran IPS, inkuiri sosial, pendidikan karakter, SD.